FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR BAHASA INGGRIS MAHASISWANON-PENDIDIKAN BAHASA INGGRIS - Dauyah, Ema; Yulinar, Yulinar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Serambi Mekkah, 2018)
The purpose of this study is to identify the factors that affect the students motivation of Non-English studentâs of Teacher Training and Education Faculty (FKIP), Universitas Abulyatama. It also aims to evaluate which of the subfactor of motivation gives more impact towards thestudents learning. The study utilized the qualitative research methodby incorporating the questionnaire which consisted of 2 factors of intrinsic motivation and 3 factors of extrinsic motivation where each of sub factor consisted of 10 questions. The questionnaire was in the form of Likert Scale.The sample was 50 students from different major of FKIP that was chosen by using purposive random sampling. The data from the questionnaire was analysed by using statistical procedure and explained descriptively. The finding showed that the extrinsic motivation was more contributive towards thestudentsâ motivation (39,66) compared to intrinsic factor (36,65). The result also showed that two sub factor of extrinsic motivation; quality of the lecturer and teaching learning (40,2) and the supporting learning facilities (39,6) were two dominant factors that can improve the students motivation.Thus, This result gives the the implication on what should be consider in the language learning especially in learning English. As such, the quality of the lecturer and the learning facilities should be improved as it will increase the students motivation in the language learning